Pengaruh Konsentrasi Maltodekstrin dan Tween 80 Terhadap Karakteristik Bubuk Minuman Instan Bunga Gumitir (Tagetes erecta L.) - Ayu Nila Ratna, Ni Komang; Diah Puspawati, Gusti Ayu; Mayun Permana, I Dewa Gede (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i04.p21, 2021)
The purpose of this research was to determine the effect of the concentration of maltodextrin and tween 80 on the characteristics of the gumitir flower instant drink powder and to proper concentration of maltodextrin and tween 80 to get the gumitir flower instant drink powder with the best characteristics by foam mat drying method. The research used two factor Randomized Block Design. First factor was concentration of maltodextrin that consisting of 3 levels (10%, 15% and 20%) and second factor was concentration of Tween 80 that consisting of 3 levels (0.3%, 0.5% and 0.7%) so there were 9 treatment combinations. The repetition of each treatment combination was carried out 2 times, in order there were 18 experimental units. The data were analyzed statistically usingthe variance test and if the treatment had a significant effect to observed variables, it was continued with Duncan's Multiple Range Test. The result showed that interaction of the concentration of maltodextrin and tween 80 had a significant effect (P<0,05) on moisture content, ash content, total dissolved solids, solubility, total phenol, total carotene, antioxidant activity, hedonic of color, scoring of aroma and scoring of taste. The concentration of 10% maltodextrin and 0.7% tween 80 was the best treatment to produce gumitir flower instant drink powder with the moisture content 3.94%, ash content 1.23%, total dissolved solids 15.2oBrix, solubility 92.18%, total phenol 93.29 mg GAE/g powder, total carotene 19.2 mg/g powder, antioxidant activity of powder 78.56% with IC50 valued 1195.72 ppm, sensory assessment of the aroma was preferred with characteristic aroma of gumitir flowers, the taste was preferred with characteristic taste of gumitir flower, the color was preferred and the overall acceptance was preferred.